Functional Engagement and Its Relationship to Hope-Based Thinking for Kindergarten Teachers (Journal Of Educational and Psychological Researches, 2023)
The research aims to identify the level of functional engagement and hope-based thinking of kindergarten teachers, identify if there is a significant difference in functional engagement and hope-based thinking in terms of specialization and years of service for kindergarten teachers, identify if there is a significant correlation between functional engagement and hope-based thinking of kindergarten teachers. The current research is determined by kindergarten teachers in the Second Rusafa Baghdad Education Directorate for the academic year (2022-2023). In order to achieve the objectives of the research, the researcher prepared a functional engagement scale, which consists of (45) items in three areas: Perceptual and functional engagement consists of (15) items, emotional engagement consists of (17) items, physical or material engagement consists of (13) items. The scale was presented to a group of experts in the field of educational and psychological sciences and the field of kindergartens, and the scale of hope-based thinking designed by Snyder (1991) was adopted. The results showed that the research sample has functional engagement and hope-based thinking at a high level. There is a statistically significant positive correlation between functional engagement and hope-based thinking. There is no significant difference in functional engagement and hope-based thinking in terms of specialization (kindergarten, other specialization). There is a significant difference in functional engagement and hope-based thinking in terms of years at range (1-10) years